МОРФОЛОГИЧЕСКИЙ СТРУКТУРНО-СЕМАНТИЧЕСКИЙ АНАЛИЗ КОНЦЕПТА «ЦЕЛЬ» В АНГЛИЙСКОМ И УЗБЕКСКОМ ЯЗЫКАХ (Scientific journal of the Fergana State University, 2024)
This article provides information about the field of comparative linguistics, which includes current issues of modern linguistics, and the researches of scientists who have recorded their research examples in this field. At the same time, the article compares lexically the linguistic units that realize the concept of "goal" in English and Uzbek, and their field nature is comparatively studied in different system languages. Lexical language units in the field of the target concept are analyzed using examples from various literature. At the same time, similar and dissimilar aspects of lexical units in both languages are analyzed in detail.